A systematic literature review of Lean Six Sigma in financial services: key finding and analysis. (3rd July 2020) - Sreedharan, V. Raja; Pattusamy, Murugan; Mohan, Smriti; Persis, D. Jinil
The paper intends to analyse the impact of LSS in financial services through systematic literature review and identify current research gaps. It focuses more on exploring the different concepts in the area of financial services by performing a systematic literature review along with data visualisation techniques. The literature review of articles that are published in peer-reviewed scholarly journals from 1993 to 2017 was collected for performing the content analysis. Based, on the descriptive analysis performed on the collected materials, many results about the articles trend in the selected areas were found. Further, the content analysis revealed many research inferences like the role of e-banking, success factors, barriers in the context of LSS. Further, proposed work for future researchers in this field. The paper presents a systematic and unique application to detect the various opportunities for LSS in the financial domain.